Comparative effects on storage period of varieties Pineapple fruits - Ali, Shah Md Yusuf; Ahiduzzaman, Md; Akhter, Sharmin; Biswas, M Abdul Matin; Iqbal, Nafis; Onik, Jakaria Chowdhury; Rahman, M Hafizur (Research in Agriculture Livestock and Fisheries, 2015)
Pineapple is considered as one of the most wanted tropical fruits and it is widely taken for fresh consumption as well as their flesh and juice are used for preparation of different product in Agro-processing industries. For such industrial processes, it is important to know the information of characteristics changes of pineapple during day after storage. Four varieties of pineapple were collected from different areas of Bangladesh named Honey Queen (H.Q), Giant Kew (G.K), Asshini and Ghorasal. Some Physico-chemical properties (weight loss, moisture content, ash and edible portion, pH, TSS, titrable acidity (TA), total sugar, reducing sugar) biochemical properties (ascorbic acid) and sensorial attributes (color, odor, firmness, appearances, sweetness and overall acceptability) of pineapple juice were studied during day after storage. This study examined the Comparison of different varieties of pineapple fruit characteristics and sensory quality of the pineapple fruits during storage. It was shown that there was a significant changes between the storage periods in relation to different varieties of fruits. The firmness of pineapple fruits were in outside and inside to be 0.21 to 0.27 N/m2 and 0.06 to 0.10 N/m2, respectively. The pH values of different varieties were found to be in the range of 4.30 to 4.36. The highest and lowest sweetness index were estimated to be 36.30 and 22.15 for Honey Queen and Asshini respectively. The highest and lowest magnitude of sugar contents of four pineapple varieties were found to be in the range of 14.16 to 15.8 mg/100g.The average TSS values were found to be 15.12%, 12.33%, 13.14% and 12.95% for H.Q., G.K., Asshini and Ghorashal, respectively. The comparative study indicated the characteristics of different varieties of pineapple changes during after storage. Res. Agric., Livest. Fish.2(3): 395-410, December 2015